الثقافة البيئية للأسرة الليبية وانعكاسها على الوعي البيئي لأبنائها ( دراسة ميدانية على طلاب المرحلة الثانوية بمدينة الجميل ) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Abstract: The environment has remained the main concern of everyone with insight into the course of life and its mark in the time of technological progress and the development of life from simple to complex, and the accompanying human interventions by changing some of the rules to which the natural environment applies, such as animals and their whereabouts, to manufactures and materials of them and how and where to dispose of them, and the trend towards them by exploiting, protecting and maintaining them and their balance, and as long as man makes all that, the positive and negative thing towards it depends on the culture adopted by society about it, and perhaps the family, perhaps, is the first to provide children with their role of environmental awareness. In our research we will focus on differentiating between the cognitive theory and the actual practical; i.e. culture and family education with children through the actual level of environmental awareness they have who are in the secondary stage of education in the city of Ajmail in the State of Libya, and by seventy-nine male and female respondents, using the descriptive analytical approach with a relative random sample, and to collect information, a questionnaire form was prepared to obtain information and then results, and one of the most important results is that the actual level of environmental awareness came First, with a high degree and with the highest arithmetic average, followed by secondly maintaining the balance of ecosystems and not depleting natural resources, then came the third family environmental education, and finally the exploitation of natural resources and the protection of the environment and its protection from pollution and depletion, both of which are moderate, and one of the results is also the existence of a positive correlation between the dimensions of family education environmentally at the actual level of environmental awareness of children, as well as the total degree of family education at the actual level of environmental awareness of children, and there are no statistically significant differences between the average ranks of each Dimensions (exploitation of natural resources, protection of the environment and protection from pollution and depletion - maintaining the balance of ecosystems and not depleting natural resources - environmental family education - the actual level of environmental awareness) among male and female students.
Keywords: culture; environment; awareness; environmental culture; environmental awareness; environmental education